2011
DOI: 10.1111/j.1440-1843.2011.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung composition and regional perfusion and tissue distribution in patients with ARDS

Abstract: Background & objective ARDS is characterised by bilateral pulmonary infiltrates and refractory hypoxemia attributed to V/Q mismatch. We used dynamic CT to characterise changes in lung composition, regional perfusion and tissue distribution in patients with ARDS in comparison to healthy subjects. Methods The Fick principle was applied to serial attenuation measurements constructed from sequential CT images acquired during the passage of a bolus of iodinated contrast medium in healthy subjects (n=3) and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Examples of clinical conditions with hypoxaemia due to large intrapulmonary shunts are extensive atelectasis, severe pneumonia and ARDS. In these conditions, the shunt might exceed 50% of total lung blood flow [13,[16][17][18][19]]. …”
Section: Shuntmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of clinical conditions with hypoxaemia due to large intrapulmonary shunts are extensive atelectasis, severe pneumonia and ARDS. In these conditions, the shunt might exceed 50% of total lung blood flow [13,[16][17][18][19]]. …”
Section: Shuntmentioning
confidence: 99%
“…Several studies have shown that arterial hypoxaemia in these patients is mostly caused by shunt blood flow that might exceed 50% of cardiac output [13,[16][17][18][19]. Low V9A/Q9 regions are either absent or a lesser cause of low PaO 2 [16,17].…”
Section: Ardsmentioning
confidence: 99%
“…First, Dakin et al [17] performed a sequence of 15 cardiac-gated single-slice CT scans while infusing intravenous contrast in 11 ALI/ARDS patients. First, Dakin et al [17] performed a sequence of 15 cardiac-gated single-slice CT scans while infusing intravenous contrast in 11 ALI/ARDS patients.…”
Section: Studies Implementing Innovative Computed Tomography Techniquesmentioning
confidence: 99%
“…Key Words: acute lung injury; PET; 18 Assessment of lung perfusion is critical for evaluating the pathophysiology of gas exchange abnormalities and can be performed noninvasively with several imaging tools: SPECT (1), PET (2-4), 4-dimensional CT (5,6), and MR imaging (7,8). PET is particularly attractive because of its high sensitivity and ability to track many other lung pathophysiologic processes (in addition to perfusion), such as ventilation (9,10), ventilation-to-perfusion ratio (11,12), and inflammation (13,14).…”
mentioning
confidence: 99%